Strategi Pengembangan Objek Wisata Pantai Batakan Baru di Desa Batakan Kecamatan Panyipatan Kabupaten Tanah Laut - Noor Saddiq, M. Mirza; Fahrati, Eny (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims determine internal factors strengths and weaknesses in development of New Batakan Beach tourist attractions, external factors opportunities and threats in development of New Batakan Beach tourist attractions, the right development strategy for New Batakan Beach tourist attractions. Respondents amounted to 74 tourist and respondents who were considered experts amounted to 6 respondents. Using SWOT Analysis. The results showed the right development strategy for New Batakan Beach tourist attraction is S-O strategy, which means using strength to take advantage opportunities so that the development program can on target, namely: Improving and maintaining the beauty of natural scenery and fresh air makes tourists comfortable and strategic tourist locations so that they are easily accessible to tourists. Increased government support in development of tourist attractions such as the construction of camping places around the outskirts New Batakan Beach tourist attraction.